Mysticism: a way of unknowing - C. E. T. Kourie (Acta Theologica)
The phenomenon of mysticism has been a cause of intense debate for philosophers, religionists, and theologians for centuries. Interest in mysticism is particularly vibrant in the 21st century, not only among the afore-mentioned, but also from other diverse sectors of society. This is evidenced in the plethora of material dealing with various aspects of mysticism. Negative or apophatic mysticism is eliciting greater attention, both in the academy and in society in general and many of the misconceptions surrounding this concept are currently under scrutiny. It is clear that apophatic mysticism — the “way of unknowing” or “nothingness” — belongs to the essence of the spiritual path. A short survey of this concept in some of the major religious traditions, together with an analysis of the place of apophasis in Christianity, brings this pertinent area of study into greater focus.